2019
DOI: 10.1155/2019/1617685
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Steering Tapered Fiber-Optic Device with Liquid Crystal Cladding

Abstract: The paper presents the results of design, manufacturing, and characterization of a hybrid broad band in-line fiber-optic device. It uses nematic liquid crystal as cladding with electro-steering properties in a biconical optical fiber taper structure. Liquid crystal mixtures denoted as 6CHBT and E7 are designed for electric as well as temperature control of electromagnetic wave propagation in a broad wavelength range. The applied taper with 10±0.5 μm diameters has losses lower than 0.5 dB in whole investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Based on the data obtained for TOF w/o metallic film measured in air, and TOF with the cover (also in the air), it can be observed that the bimetallic cover of Au/Ag causes attenuation with a value similar to the silver layers [ 39 ]. As before, the main dips (A) are shifted from the peaks obtained for single metallic layers and are equal to 803.6 nm, = 926.4 nm, and = 968.4 nm for orthogonal, parallel, and twist, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data obtained for TOF w/o metallic film measured in air, and TOF with the cover (also in the air), it can be observed that the bimetallic cover of Au/Ag causes attenuation with a value similar to the silver layers [ 39 ]. As before, the main dips (A) are shifted from the peaks obtained for single metallic layers and are equal to 803.6 nm, = 926.4 nm, and = 968.4 nm for orthogonal, parallel, and twist, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the orthogonal cell, the absorption is the lowest and is approximately 60%. High power fluctuations are visible on the presented relations, but they are slightly lower than in the case of the single metal cover [ 14 , 39 ]. This is probably due to the deposition of a thinner metallic film, in particular the silver one ( h Ag ~ 5 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the special anti-gravity unit is used because during the elongation process the fiber position is reduced. The signal increase in the anti-gravity system is an impulse for changing drawing velocity, as well as lowering the burner position [11,12]. Additionally, by selection of a proper flame, we can make a taper with a very small dimension of the taper waist.…”
Section: Technologymentioning
confidence: 99%
“…This parameter is described as [9]:From the above formula, it can be concluded that the number of modes propagating in the fiber is also influenced by the wavelength λ and the diameter of the core a. This parameter is important when we want to use a tapered optical fiber [10][11][12] or long period gratings (LPG) [13,14] as an element of optical devices. LCs are built of elongated molecules.…”
mentioning
confidence: 99%
“…A low losses structure is obtained for an adiabatic taper characterized by a long transition region compared to the taper waist region [2]. Since a light beam is propagated in the whole structure of a taper waist without division into core and cladding, hence it is possible to influence beam propagation inside the fiber by boundary conditions modification [3]. In a structure created in this way, the taper waist region becomes the core and the surrounding medium becomes its cladding.…”
mentioning
confidence: 99%